A lightweight broadband cavity-enhanced spectrometer for NO2 measurement on uncrewed aerial vehicles - C. C. Womack; C. C. Womack; S. S. Brown; S. S. Brown; S. J. Ciciora; R.-S. Gao; R. J. McLaughlin; M. A. Robinson; M. A. Robinson; Y. Rudich; R. A. Washenfelder (Atmospheric Measurement Techniques, 2022)
We describe the design and performance of a lightweight broadband cavity-enhanced spectrometer for measurement of NO2 on uncrewed aerial vehicles and light aircraft. The instrument uses a light-emitting diode (LED) centered at 457 nm, high-finesse mirrors (reflectivity =0.999963 at 450 nm), and a grating spectrometer to determine optical extinction coefficients between 430 and 476 nm, which are fit with custom spectral fitting software and published absorption cross sections. The instrument weighs 3.05 kg and has a power consumption of less than 35 W at 25 ∘C. A ground calibration unit provides helium and zero air flows to periodically determine the reflectivity of the cavity mirrors using known Rayleigh scattering cross sections. The precision (1σ) for laboratory measurements is 43 ppt NO2 in 1 s and 7 ppt NO2 in 30 s. Measurement of air with known NO2 mixing ratios in the range of 0–70 ppb agreed with the known values within 0.3 % (slope =0.997±0.007<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="78pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="070c85d9bb34c1e2574f428ab72c4964"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-6643-2022-ie00001.svg" width="78pt" height="10pt" src="amt-15-6643-2022-ie00001.png"/></svg:svg>; r2=0.99983). We demonstrate instrument performance using vertical profiles of the NO2 mixing ratio acquired on board an uncrewed aerial vehicle between 0 and 110 m above ground level in Boulder, Colorado.